S = n = − ∞ ∑ ∞ 1 + n 2 ( − 1 ) n = e c π − 1 a π e b π ,
where a , b , c are natural numbers. Find a + b + c .
Note: Please avoid using wolfram alpha.
Hint: Think about the Fourier transform of f ( x ) = e − ∣ a x ∣ .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Thanks for posting tis interesting problem! I need more practice on Fourier Analysis.
did You Studied This Level of integration from Your Institute , or somewhere Else ? Because These are beyond the scope of JEE Advance . I much impressed from your integration skills @Pratik Shastri .And I guess I'am talking to JEE 2015 under 100 Ranker , Am I correct ?
Thank you, I learned this from wikipedia. And under 100? No way! Chemistry is a big hurdle for me. Especially inorganic chemistry.
I believe you should not give the hint in the question but anyways I have done this question in other way than yours @Pratik Shastri.
The hint doesn't give away much, does it? I mean you need to think about using the Poisson summation formula.
If this is the condition of JEE aspirants 2015, then i'm far behind from the scope of IIT :(
This problem can also be solved by the formula ∑ n = 0 ∞ n + a 1 = − φ ( a ) where φ is the Digamma Function and a is any complex number.
Well, 2 important series which I learnt sometimes before helped me here, i.e that of c o t h ( x ) and t a n h ( x ) .
Problem Loading...
Note Loading...
Set Loading...
S = n even ∑ 1 + n 2 1 − n odd ∑ 1 + n 2 1 Now, n even ∑ 1 + n 2 1 = n = − ∞ ∑ ∞ 1 + ( 2 n ) 2 1 = 4 1 n = − ∞ ∑ ∞ 1 / 4 + n 2 1 .
Also, n odd ∑ 1 + n 2 1 = n = − ∞ ∑ ∞ 1 + n 2 1 − n even ∑ 1 + n 2 1 = n = − ∞ ∑ ∞ 1 + n 2 1 − 4 1 n = − ∞ ∑ ∞ 1 / 4 + n 2 1
Hence, S = 2 1 n = − ∞ ∑ ∞ 1 / 4 + n 2 1 − n = − ∞ ∑ ∞ 1 + n 2 1 ( 1 )
Now, consider f ( x ) = e − a ∣ x ∣ , a > 0 . Let F ( k ) be the Fourier transform of f .
∴ F ( k ) = ∫ − ∞ ∞ f ( x ) e − i k x d x = ∫ − ∞ ∞ e − a ∣ x ∣ e − i k x d x = a 2 + k 2 2 a
Now according to the Poisson summation formula , n = − ∞ ∑ ∞ f ( n ) = m = − ∞ ∑ ∞ F ( m )
Therefore, n = − ∞ ∑ ∞ e − a ∣ n ∣ = m = − ∞ ∑ ∞ a 2 + ( 2 π m ) 2 2 a
The LHS is just a geometric series. Summing it, we get
m = − ∞ ∑ ∞ a 2 + ( 2 π m ) 2 2 a m = − ∞ ∑ ∞ ( a / 2 π ) 2 + n 2 1 = 1 − e − a 1 + e − a = a 2 π 2 1 − e − a 1 + e − a
Put a = 2 π , π / 2 and substitute the results into ( 1 ) to obtain S = e 2 π − 1 2 π e π